Synthesis of Manganese Dioxide Nanoparticles by Plant Extract Mediated and their Effect on Biofilm Formation - Sabeha, Sabeha; J. Shanan, Zainab (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
In the current work, Punica granatum L. peel, Artemisia herba-alba Asso., Matricaria chamomilla L., and Camellia sinensis extracts were used to prepare manganese dioxide (MnO2) nanoparticles utilizing a green method. Energy-dispersive X-ray (EDX) analysis, Fourier Transform Infrared Spectroscopy (FTIR) analysis, and Filed emission-scanning electron microscopy (FE-SEM) analysis were used to evaluate the produced MnO2 NPs. FE-SEM pictures demonstrated how agglomerated nanoparticles formed. According to FE-SEM calculations, the particle size ranged from 18.7-91.5 nm. FTIR spectra show that pure Mn-O is formed, while EDX results show that Mn and O are present. The ability to suppress biofilm growth in the produced MnO2 NPs was examined. The outcomes showed that both bacterial and fungal biofilms were effectively inhibited by the MnO2 NPs produced.